The Gambia Economic Update, December 2020 : Preserving the Gains - World Bank (World Bank, Washington, DC, 2021)
Real GDP growth exceeded 6 percent during the two years before COVID-19 (coronavirus) struck, supported by rebounding confidence, investment, low interest rates, and growing tourism. Investment accounted for over 22 percent of GDP in 2019, three-fifths of which was private. The tourism market had weathered the collapse of Thomas Cook UK and expanded into new markets. Industry was the fastest-growing sector in 2019, partly due to the issuance of oil-prospecting licenses, but also due to strong investment in construction fueled by remittances from the diaspora. On the other hand, agriculture had contracted, affected by erratic rainfall and the late supply of inputs. Tourism arrivals had started the year in line with 2019 but collapsed by 50 percent in March and are expected to fall by 63 percent in 2020. However, official remittances grew at record pace in the second quarter, perhaps due to travel restrictions closing informal channels. Favorable rainfall, good access to inputs, and few pest outbreaks bode well for agriculture. It registered the lowest fiscal deficit since 2009 and a primary surplus after 2009. This came despite increased expenditure, as revenues rose due to increased excises and levies and improved revenue administration capacity. Both budget and project grants also increased. The Government continues to make large transfers to state-owned enterprises (SOEs), however, the fiscal burden of which is estimated to be around 6 percent of 2019 GDP. Pressures from COVID-19 saw the deficit rise in the first half of 2020 although the tax authorities still managed to exceed their revised collection targets. Tax exemptions, although declining, continue to be sizeable-without discretionary exemptions, the deficit in the first half of 2020 would have been reduced by 0.7 percent of GDP. Non-tax revenue has been boosted by one-off items such as the sale of assets, which partly compensated for the tax decline. The Government initially responded to pandemic-related spending pressures through budgetary reallocation. In July, the National Assembly passed a supplementary bill aimed at providing further relief and stimulating recovery.